Organizational Culture: Can It Be a Source of Sustained Competitive Advantage? - Barney, Jay B. (Academy of Management Review, 1986)
Three attributes that a firm's culture must have to generate sustained competitive advantages are isolated. Previous findings suggest that the cultures of some firms have these attributes; thus, these cultures are a source of such advantages. The normative implications of the analysis are discussed. Firms that do not have the required cultures cannot engage in activities that will modify their cultures and generate sustained superior financial performance because their modified cultures typically will be neither rare nor imperfectly imitable. Firms that have cultures with the required attributes can obtain sustained superior financial performance from their cultures.